Estudios de casos sobre cambio tecnologico en la produccion de frijol en America Latina - Pachico, Douglas H. (International Center for Tropical Agriculture, 1987)
Case studies from Costa Rica, Guatemala, and Colombia are reviewed on improved technology adoption to find out to what degree has this technology been adapted to the needs of low income farmers, consider the relationship between new var. adoption and the changes in farm management, and examine the socioeconomic and institutional context as determinant of opportunities for technological change. The impact of new technology is substantially related to the effectiveness in seed production and distribution, markets, extension, and on-farm research. The design of improved technology for farm systems should be based on the specific biotic and socioeconomic circumstances of a place. Case studies on beans and the strategy of an approach for disease resistance for small farmers in marginal areas show that it is possibe to make progress, like in the case of Costa Rica, where bean production has doubled during the 80's. (CIAT)